(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
Behavior Analysis can be characterized as a multifaceted field of knowledge whose development depends on the constant interaction among its three domains: Experimental Analysis of Behavior, Applied Behavior Analysis, and Radical Behaviorism. First, we describe how, throughout the historical construction of the field, applied behavior analysts carried out interventions intended to modify sexual and gender behaviors that were socially considered as inappropriate—specifically, non-heterosexual and non-cisgender behaviors—in alignment with the cisheteronormative culture. Second, we aim to demonstrate how these works, which were harmful to LGBT+ population, although reflecting the historical period in which they were conducted, were in many respects an evident contradiction when considered in light of the philosophical assumptions of Radical Behaviorism. Moreover, such inconsistency was, at the time, immediately denounced by behavior analysts committed to integrating the three aforementioned domains.